2017
DOI: 10.1097/mpg.0000000000001427
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Maternal Milk on Tolerance and Growth in Premature Infants

Abstract: In preterm infants, an association between type of feeding (human milk vs infant formula) and time to achieve full enteral feeding or short-term growth was not found. Future prospective trials are needed to verify our results and focus on means to improve tolerance further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…A total of 18 articles were selected, of which eight were experimental studies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ] and the remaining ten were observational studies [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ] ( Figure 1 ). The characteristics of the applied interventions are presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 18 articles were selected, of which eight were experimental studies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ] and the remaining ten were observational studies [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ] ( Figure 1 ). The characteristics of the applied interventions are presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…An indirect sign of good feeding tolerance is growth (increase in length, weight, and HC of neonates). In fact, Hogewind-Schoonenboom et al [ 34 ] evaluated the association of the amount of fortified BM or FM with feeding tolerance and growth in preterm infants. Among their results, they identified that residual gastric volumes were significantly lower in the group that received the least amount of BM (as they divided the sample according to the percentage of feeding from the mother and FM).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations